Mapping Research on Artificial Intelligence in Education: A Bibliometric Analysis - Hidayat, M Topit; Armiati, Armiati; Noviani, Cyindi (Yayasan Keluarga Guru Mandiri, 2026)
This research aims to explore the development of academic publications on artificial intelligence (AI) in education. Using bibliometric analysis, this research examines scientific publications indexed in Scopus from 2020 to 2024. The primary keyword utilized for data collection is